Response of growth and digestive organs development of Pelung x Kampung crossbred chicken to dietary proteins - Iskandar, Sofjan (Indonesian Journal of Animal and Veterinary Sciences, 2004)
More information on the performance of local breed of chicken encourages more exploration on early digestive tract development of Pelung x Kampung cross chicken. One hundred and sixty day-old chicks (doc) of Pelung x Kampung crossbred were sexed and allocated to two different dietary proteins of 15 or 19% with the same level of dietary energy (2900 kcal/kg) and other nutrients according to levels suggested for light high breed chicken. Rations, in a form of mash, and water provided ad libitum during the 28 days of observation. Body weight and feed consumption were recorded weekly. Thirty-two day old chickens were sacrificed for digestive track analysis, then two chickens obtained from each trial replicate were also sacrificed at day 7, 14, 21 and 28, following at least 3 hours of starvation to clear the tract from remaining digesta. The cut organs (crop, proventriculus, gizzard, duodenum, jejunum, ileum and caecum) were separated and cleaned carefully from digesta with tissue paper prior to weighing. Number of birds in each cage was rearranged to keep the number relatively the same throughout the replicates every week after sacrificing. Higher body weight of young chicken to 19% dietary protein compared to 15% dietary protein was shown at 28 days of age. Gizzard, duodenum, jejunum and ileum developments of male chicks were significantly higher than that of females when the chicks reached the age of 28 day. Generally the relatif weight of duodenum and jejunum were relatively higher than the development of growth or development of other digestive organ segmens. Response of other observed parameters other than mentioned above to dietary protein nor sex were not significantly different at any other ages. Â  Key words: Pelung x Kampung crossbred chicken, growth, digestive organs developments, dietary proteins